2000
DOI: 10.1016/s0002-9440(10)64802-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α1β1 and Transforming Growth Factor-β1 Play Distinct Roles in Alport Glomerular Pathogenesis and Serve as Dual Targets for Metabolic Therapy

Abstract: Alport syndrome is a genetic disorder resulting from mutations in type IV collagen genes. The defect results in pathological changes in kidney glomerular and inner-ear basement membranes. In the kidney, progressive glomerulonephritis culminates in tubulointerstitial fibrosis and death. Using gene knockout-mouse models, we demonstrate that two different pathways, one mediated by transforming growth factor (TGF)-beta1 and the other by integrin alpha1beta1, affect Alport glomerular pathogenesis in distinct ways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
179
0
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 53 publications
7
179
0
8
Order By: Relevance
“…The inability to affect kidney function was attributed to the failure to inhibit effacement of the podocyte processes caused by improper composition of the Col4A3-deficient glomerular basement membrane (GBM). 7 Consistent with these findings, we observed podocyte effacement and GBM alterations by transmission electron microscopy in kidneys of the Col4A3 Ϫ/Ϫ ;␤6 Ϫ/Ϫ mice (data not shown). These findings indicate that inhibition of the TGF-␤ pathway does not alter the structural integrity of the GBM in Alport mice.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The inability to affect kidney function was attributed to the failure to inhibit effacement of the podocyte processes caused by improper composition of the Col4A3-deficient glomerular basement membrane (GBM). 7 Consistent with these findings, we observed podocyte effacement and GBM alterations by transmission electron microscopy in kidneys of the Col4A3 Ϫ/Ϫ ;␤6 Ϫ/Ϫ mice (data not shown). These findings indicate that inhibition of the TGF-␤ pathway does not alter the structural integrity of the GBM in Alport mice.…”
Section: Discussionsupporting
confidence: 83%
“…Cloned heavy and light chain variable regions were ligated into mammalian expression vectors with human IgG1 constant regions. Recombinant soluble murine TGF-␤ receptor type II-Ig fusion protein (rsTGF-␤RII-Ig) was generated as previously described 7 and purchased from R&D Systems (532-R2; Minneapolis, MN). Antibodies were purchased as indicated: fluorescein isothiocyanate-conjugated pan anti-cytokeratin mAb (C-11; F3418) from Sigma-Aldrich (St. Louis, MO); anti-laminin B1 chain mAb (LT3; MAB1928) from Chemicon (Temecula, CA); phycoerythrin (PE)-conjugated anti-␣v mAb (RMV7; CBL1346P) from Chemicon; rabbit anti-␣v from Chemicon (AB1930); PE-rat IgG1 (553925) from BD Biosciences (San Jose, CA); and anti-smooth muscle actin (SMA)-Cy3 from Sigma-Aldrich (C-6198).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first pathway is TGF-␤ 1 -stimulated and has been well established in many other disease models as well (7)(8)(9)(10)(11). The second pathway is ␣ 1 ␤ 1 integrin-dependent (12). The ␣ 1 ␤ 1 integrin is a major integrin receptor expressed on mesangial cells, and Cosgrove et al (12) hypothesized that loss of ␣ 1 integrin expression on the mesangial cells resulted in the abnormal expression of specific laminin isoforms.…”
mentioning
confidence: 99%
“…The second pathway is ␣ 1 ␤ 1 integrin-dependent (12). The ␣ 1 ␤ 1 integrin is a major integrin receptor expressed on mesangial cells, and Cosgrove et al (12) hypothesized that loss of ␣ 1 integrin expression on the mesangial cells resulted in the abnormal expression of specific laminin isoforms. Focusing on glomerular pathogenesis, these authors demonstrated that mesangial expansion and podocyte foot process effacement are attenuated in Alport's animals lacking the ␣ 1 ␤ 1 integrin.…”
mentioning
confidence: 99%